2012
DOI: 10.1080/15374416.2012.651993
|View full text |Cite
|
Sign up to set email alerts
|

Attention Mechanisms in Children with Anxiety Disorders and in Children with Attention Deficit Hyperactivity Disorder: Implications for Research and Practice

Abstract: Inattention is among the most commonly referred problems for school-aged youth. Research suggests distinct mechanisms may contribute to attention problems in youth with anxiety disorders versus youth with attention deficit hyperactivity disorder (ADHD). This study compared children (8-17 years) with anxiety disorders (n = 24) and children (8-16 years) with ADHD (n = 23) on neurocognitive tests of both general and emotion-based attention processes. As hypothesized, children with ADHD demonstrated poorer selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…In addition, most SMD youth have co‐occurring ADHD; another limitation of this study is the absence of an ADHD comparison group. Emotion‐attention interactions in ADHD are not well understood, although other studies have not found evidence of threat bias in youth with ADHD or other disruptive behavior disorders (DBDs) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, most SMD youth have co‐occurring ADHD; another limitation of this study is the absence of an ADHD comparison group. Emotion‐attention interactions in ADHD are not well understood, although other studies have not found evidence of threat bias in youth with ADHD or other disruptive behavior disorders (DBDs) …”
Section: Discussionmentioning
confidence: 99%
“…Emotionattention interactions in ADHD are not well understood, although other studies have not found evidence of threat bias in youth with ADHD or other disruptive behavior disorders (DBDs). [13,44,51] Including nonirritable youth with DBDs, such as ODD and ADHD, would speak to the specificity of attention biases to irritability, rather than to ODD or ADHD. Unfortunately, we were not able to address this question in the current study because approximately 85% of SMD youth met criteria for either ODD, ADHD, or both, making any comparative analyses underpowered.…”
Section: Depression and Anxietymentioning
confidence: 99%
“…However, the extant work directly comparing EF performance across neuropsychiatric disorders yields mixed findings. 1622 For example, some studies document worse EF performance in youth with ADHD compared to youth with anxiety disorders 19 ; however, other work finds no such EF differences. 20 …”
Section: Introductionmentioning
confidence: 99%
“…For example, Weissman and colleagues (2012) compared the performance of anxious, inattentive-impulsive, and typically developing children on several neurocognitive tasks assessing attentional processes. The authors found that inattentive-impulsive youth performed more poorly on tests of general attentional processes, as measured by the Conners’ Continuous Performance Test (CPT-II), than anxious children and typically developing controls.…”
Section: Introductionmentioning
confidence: 99%